IMPLEMENTING CASE STUDIES TO DEVELOP THE SOCIOLINGUISTIC COMPETENCE OF FUTURE JOURNALISTS (Journal of Universal Science Research, 2023)
The concept of communicative competence is seen as a complicated polymorphic concept that integrates a variety of competencies in the context of an intercultural approach to teaching foreign languages. One of the most crucial skills for future journalists is sociolinguistic competency. Sociolinguistic competence refers to the capacity to interact with people at their level of development and be aware of non-traditional elements like the culture, way of life, accepted social norms, history, and other social contexts of the speakers of the language with which they interact, plays a role in ensuring successful communication. The focus of the article is to help aspiring English instructors hone their sociolinguistic skills through case studies. Additionally, different case study types, their elements, and the circumstances surrounding language acquisition adaption are taken into account.